Analysis of Challenges and Opportunities for Tax Reform in Indonesia: The Role of Education - Sri Hutami Adiningsih S; Ika Wisudawaty; Wulan Purnamasari (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
Tax reform in Indonesia represents a strategic government effort to develop a modern, fair, transparent, and adaptive tax system amid global economic dynamics. This study employs a qualitative literature review to examine tax concepts, reform theories, Indonesian tax policies, and relevant previous research. The findings show that tax reform faces key challenges, including low taxpayer compliance, regulatory uncertainty, limited digital infrastructure, and the persistence of a large informal sector. Despite these challenges, tax reform offers substantial opportunities through tax system digitalization, tax base expansion, tariff structure improvement, and strengthened international cooperation. This study emphasizes the crucial role of education in enhancing tax literacy, encouraging voluntary compliance, and supporting effective tax reform implementation. Both formal and non-formal education contribute to increasing taxpayer awareness, understanding, and trust in tax obligations. Further analysis indicates that education-supported tax reform positively impacts the national economy by increasing state revenue, improving the investment climate, promoting income distribution, and supporting sustainable development. Therefore, tax reform is not merely an administrative process but a long-term strategy that requires strong educational support to ensure fiscal stability and sustainable economic growth in Indonesia.